Formulasi dan Uji Efektivitas Ekstrak Bayam Duri (Amaranthus spinosus L.) Sebagai Krim Antibakteri Terhadap Bakteri Cutibkterium acnes dan Staphylococcus aureus - Anna miroh Daulay; Rasyidah Rasyidah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Acne vulgaris is a common skin problem in adolescents that often causes stress, anxiety, and decreased self confidence. Spiny Amaranth (Amaranthus spinosus L.) has antibacterial potential, but its effectiveness against Cutibacterium acnes has not been fully explored. This study aims to develop a cream formulation of Spiny Amaranth leaf ethanol extract and test its antibacterial effectiveness against Cutibacterium acnes and Staphylococcus aureus. The research method includes extraction of Spiny Amaranth leaves, cream preparation, and antibacterial activity test using the disc diffusion method. The results showed that the antibacterial cream of Spiny Amaranth leaf extract has good effectiveness against the growth of Cutibacterium acnes and Staphylococcus aureus, with an increasing inhibition zone along with the increase in extract concentration, namely 18.5 mm at 25% concentration and 27.9 mm at 50% concentration for Cutibacterium acnes, and 16.0 mm at 25% concentration and 23.3 mm at 50% concentration for Staphylococcus aureus. The characteristics of the cream that are suitable for the skin and the stable emulsion type make this cream ideal for skin application. The results of this study indicate that the antibacterial cream of Spiny Amaranth leaf extract can be used as an effective alternative natural antibacterial treatment.